2021
DOI: 10.1080/0142159x.2021.1902966
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating medical student stress and anxiety: Should schools mandate participation in wellness intervention programs?

Abstract: Purpose: Medical students are at increased risk of poor mental health and need to regularly engage in preventive programs to maintain well-being. However, many do not and it remains an open question whether these programs should be mandatory. We implemented a RCT to examine the effectiveness of assigning medical students to a wellness intervention on adherence to engagement in the assigned intervention and on psychological and academic outcomes. Method: Medical students participated in a 12-week randomized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 56 publications
0
38
1
4
Order By: Relevance
“…Most of the studies describe the relationship between anxiety and wellness as a negative relationship. However, this study showed a positive relationship, which is possibly due to anxiety in this study being within the normal range ( 37 ).…”
Section: Discussioncontrasting
confidence: 50%
“…Most of the studies describe the relationship between anxiety and wellness as a negative relationship. However, this study showed a positive relationship, which is possibly due to anxiety in this study being within the normal range ( 37 ).…”
Section: Discussioncontrasting
confidence: 50%
“…And even more, medical students are at a higher rate of mental health problems than non-medical undergraduates, such as anxiety, depression, stress, suicide and so on ( 8 ). These problems might lead to a range of adverse effects, such as poor academic performance, bad relationships with peers, and increasing risk of suicide and non-suicidal self-injury (NSSI) behavior ( 9 , 10 ). Moreover, they might also potentially increase the incidence of drug abuse, medical errors, and unethical behavior after graduation ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various aspects of student personalities, including professionalism and communication skills, general academic preparation, and external forces such as life events, are likely to play a significant role in student performance in dental school, 9,19 and a holistic approach to supporting matriculated dental students is warranted. Stress has also been shown to have a negative association with GPA, 20 but wellness interventions reduce perceived anxiety and stress 21 . A humanistic approach to dental school curricula and student services is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Stress has also been shown to have a negative association with GPA, 20 but wellness interventions reduce perceived anxiety and stress. 21 A humanistic approach to dental school curricula and student services is warranted. Dental schools should offer resources such as academic advisement, tutoring, and services such as study skills seminars.…”
Section: Discussionmentioning
confidence: 99%